2020
DOI: 10.1155/2020/7890985
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Adoptive TIL Therapy plus Anti-PD1 Therapy in Patients with Chemotherapy-Resistant Metastatic Osteosarcoma

Abstract: Background. The pathological subtype of osteosarcoma is one of the most common malignant bone tumors. Notably, chemotherapy-resistant metastatic osteosarcoma has been reported to cause significant mortality and shows poor prognosis with the currently available multidisciplinary treatments. This study investigated whether combined adoptive TIL and anti-PD1 therapy improves the prognosis of patients with chemotherapy-resistant metastatic osteosarcoma. Methods. A total of 60 patients with chemotherapy-resistant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Although osteosarcoma patients with DM dramatically develop more lesions and become resistant to chemotherapy (14), underscoring a critical need for new treatments strategies, continuous chemotherapy still plays an important role in prolonging patients' life and several clinical trials are still ongoing (41,42). Surgery alone, the only effective way to treat osteosarcoma decades ago, which consisted of removing the tumor of amputating, didn't reduce mortality below 80%, but there is still a place for osteosarcoma patients with DM (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although osteosarcoma patients with DM dramatically develop more lesions and become resistant to chemotherapy (14), underscoring a critical need for new treatments strategies, continuous chemotherapy still plays an important role in prolonging patients' life and several clinical trials are still ongoing (41,42). Surgery alone, the only effective way to treat osteosarcoma decades ago, which consisted of removing the tumor of amputating, didn't reduce mortality below 80%, but there is still a place for osteosarcoma patients with DM (1).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20-30% of osteosarcoma patients presented clinical DM (most commonly in the lung) at the time of the first diagnosis (10,11), and about 25-35% of patients with initially non-metastatic osteosarcoma subsequently develop metastatic diseases (12,13). Of note, osteosarcoma patients with DM promptly develop more lesions and become resistant to chemotherapy (14), with dismal 5-year overall survival (OS) time less than 20% (15). Therefore, it is imperative to construct exact models to assess the risk of DM of osteosarcoma patients and evaluate the prognosis of patients with DM.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the TARGET database using 27 matched osteosarcoma patient samples assessed changes in the immune environment after chemotherapy and found that neoadjuvant chemotherapy was associated with increased infiltration of all T cells, and specifically CD8 + T cells, into the tumors, with decrease in myeloid-derived suppressive cells 82 . Additional work has found that genomic instability of osteosarcoma leads to neoantigen generation, potentially making it more immunogenic or “hot”; in this study, increased TILs were found in metastatic disease compared with the primary tumor, hinting a use for T-cell–based immunotherapy in metastatic osteosarcoma 83 . Two active trials using TIL therapy along with lymphodepleting chemotherapy and post-TIL IL-2 are currently enrolling patients as young as 16 years old (NCT03449108, NCT04052334).…”
Section: Investigation Of Tils In Pmst: Preclinical and Early Clinicalmentioning
confidence: 49%
“…treated 60 patients with metastatic osteosarcoma previously treated with chemotherapy with nivolumab q2weeks and injected individual patient derived cultured TILs from fresh tumour biopsies. The ORR by response evaluation criteria in solid tumours (RECIST) 1.1 was 36.7% (n = 22/60, 2 complete response (CR) and 20 partial response (PR)), with the median progression free (mPFS) and overall survival (mOS) 5.6 months and 13.6 months respectively for the entire population [53] . Patients with an objective response had a longer mPFS (8.9 months) and mOS (23.7 months).…”
Section: Clues For a Future Role For Immunotherapymentioning
confidence: 99%